Sharecropping and economic efficiency in Bangladesh - Zaman, M. Raquibuz; Bangladesh Institute of Development (Dacca, Bangladesh : Bangladesh Institute of Development Economics, 1972)
The main purpose of the study is to test the implications of traditional and ideal leases on the economic efficiency of crop sharing vis-a -vis owner farming
Includes bibliographical references.
obn 24/01/2019
Loans
Keywords: Sharecropping; Bangladesh